Conference Report. Gender Equality in the Arctic. Current Realities, Future Challenges. - Oddsdóttir, Embla Eir; Sigurðsson, Atli Már; Swandal, Sólrún; Árnadóttir, Anna Kolbrún (Ministry for Foreign Affairs, Iceland in cooperation with Icelandic Arctic Cooperation Network and the Centre For Gender Equality, 2015)
The conference was held in Akureyri, Iceland on 30-31 October 2014 with 150 participants representing various stakeholders from all member states of the Arctic Council: Canada, the Kingdom of Denmark (Greenland and the Faroe Islands), Iceland, Finland, Norway, the Russian Federation, Sweden, the United States, and representatives of the Permanent Participants. The main organizers of the conference were the Ministry for Foreign Affairs of Iceland, the Centre for Gender Equality in Iceland, the Stefansson Arctic Institute, and the Icelandic Arctic Cooperation Network in collaboration with the conference scoping committee and with the strong support of the Nordic Council of Ministers, Sweden, Finland, Norway, the Faroe Islands, the Aleut International Association, and the Arctic Council. The conference was generously sponsored by the Ministry for Foreign Affairs of Iceland, the Icelandic Government’s Equality Action Fund, the Foreign Ministry of Sweden, and the Nordic Council of Ministers.The main objective was to promote an extensive, policy relevant dialogue on gender equality putting current realities and future challenges into context with climate and environmental changes as well as economic and social developments. Another goal was to raise decision-makers’ awareness of the situation of women and men in the Arctic and to strengthen cooperation among different people working with gender issues. The Ministry for Foreign Affairs of Iceland; The Icelandic government’s Equality Action Fund; The Foreign Ministry of Sweden; The Nordic Council of Ministers.